Evaluation of non-response in quality control of nasal septal surgery. Issue 12 (27th October 2016) - Egeland, M T; Tarangen, M; Gay, C; Døsen, L K; Haye, R
Abstract: Objective: Questionnaires are often used to assess the results of nasal septoplasty, but response rates vary widely. The possible bias caused by non-responders was evaluated to determine the validity of questionnaire results. Methods: Post-operative questionnaires employing visual analogue scales for nasal obstruction were mailed to 182 patients. The 62 non-responders (34.1 per cent) were contacted by telephone, 58 (93.5 per cent) of whom were contactable and responded orally to the questionnaire. Results: Non-responders were younger, but no different from responders with regard to gender, smoking habits or allergies. Post-operative visual analogue scale obstruction scores were slightly, but not statistically, higher in non-responders. However, because non-responders' pre-operative scores were lower, obstruction scores improved less than in responders. The main reason for not responding was forgetfulness. Some would have preferred an electronic version of the questionnaire. Conclusion: Although post-operative obstruction scores did not differ between the groups, nasal obstruction scores improved more among responders than non-responders. Thus, low response rates may cause bias.